2019
DOI: 10.3390/ijgi8020056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of the Spectral and Spatial Consistency of Sentinel-2 and Landsat-8 OLI Data for Igneada Longos Forest

Abstract: This study aims to test the spectral and spatial consistency of Sentinel-2 and Landsat-8 OLI data for the potential of monitoring longos forests for four seasons in Igneada, Turkey. Vegetation indices, including Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI) and Normalized Difference Water Index (NDWI), were generated for the study area in addition to the five corresponding bands of Sentinel-2 and Landsat-8 OLI Images. Although the spectral consistency of the data was interprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 41 publications
1
30
0
1
Order By: Relevance
“…Therefore, to set different threshold for OLI and MSI data should be considered in collaboration applications of the two data. Although many studies utilized various applications with different dates data and showed that a difference of less than three days does not lead to significant changes in the correlation coefficient [28,32,47], the compared result of the only one pair from the different dates in this study shows the lowest correlation and largest scatter and RMSD among all comparisons. This may be due to the presence of thin clouds which were not completely excluded by cloud removal or atmospheric correction [48] and influenced the comparison of these data pairs in summer [37].…”
Section: Comparison Of Roughly Built-up Area Identification Between Omentioning
confidence: 66%
See 4 more Smart Citations
“…Therefore, to set different threshold for OLI and MSI data should be considered in collaboration applications of the two data. Although many studies utilized various applications with different dates data and showed that a difference of less than three days does not lead to significant changes in the correlation coefficient [28,32,47], the compared result of the only one pair from the different dates in this study shows the lowest correlation and largest scatter and RMSD among all comparisons. This may be due to the presence of thin clouds which were not completely excluded by cloud removal or atmospheric correction [48] and influenced the comparison of these data pairs in summer [37].…”
Section: Comparison Of Roughly Built-up Area Identification Between Omentioning
confidence: 66%
“…The result analysis of the comparison between Landsat 8 OLI and Sentinel-2 MSI shows that these two data have good consistency while the value of R is little lower than previous studies in both bands and indices pairs [32][33][34][35][36][37]. The difference in the complex land surface in the urban area might have been caused by the influence from heterogeneity on the correlation of the two data [24].…”
Section: Analysis On the Consistency Of Bands And Indices Between Olimentioning
confidence: 73%
See 3 more Smart Citations